Efficacy and safety of finerenone in patients with chronic kidney disease and type 2 diabetes by GLP‐1RA treatment: A subgroup analysis from the FIDELIO‐DKD trial. Issue 1 (11th October 2021) - Rossing, Peter; Agarwal, Rajiv; Anker, Stefan D.; Filippatos, Gerasimos; Pitt, Bertram; Ruilope, Luis M.; Amod, Aslam; Marre, Michel; Joseph, Amer; Lage, Andrea; Scott, Charlie; Bakris, George L.; et al.
Abstract: Aims: Finerenone significantly reduced the risk of kidney and cardiovascular (CV) outcomes in patients with chronic kidney disease and type 2 diabetes in the FIDELIO‐DKD trial (NCT02540993). This exploratory subgroup analysis investigates the effect of glucagon‐like peptide‐1 receptor agonist (GLP‐1RA) use on the treatment effect of finerenone. Materials and Methods: Patients with type 2 diabetes, urine albumin‐to‐creatinine ratio (UACR) 30‐5000 mg/g and estimated glomerular filtration rate 25‐<75 ml/min per 1.73 m 2 receiving optimized renin‐angiotensin system blockade were randomized to finerenone or placebo. Results: Of the 5674 patients analysed, overall, 394 (6.9%) received GLP‐1RAs at baseline. A reduction in UACR with finerenone was observed with or without baseline GLP‐1RA use; ratio of least‐squares means 0.63 (95% confidence interval 0.56, 0.70) with GLP‐1RA use and 0.69 (95% confidence interval 0.67, 0.72) without GLP‐1RA use ( p value for interaction .20). Finerenone also significantly reduced the primary kidney (time to kidney failure, sustained decrease in estimated glomerular filtration rate ≥40% from baseline, or renal death) and key secondary CV outcomes (time to CV death, non‐fatal myocardial infarction, non‐fatal stroke, or hospitalization for heart failure) versus placebo, with no clear difference because of GLP‐1RA use at baseline ( p value for interaction .15 and .51 respectively) or any time during the trial. The safety profile of finerenone was similar between subgroups. Conclusions: This exploratory subgroup analysis suggests that finerenone reduces UACR in patients with or without GLP‐1RA use at baseline, and the effects on kidney and CV outcomes are consistent irrespective of GLP‐1RA use.